"DISMEMBERING THE HUMAN CHARACTER": ADAM FERGUSON'S CONCEPTION OF CORRUPTION. Issue 2 (9th May 2019) - Fleischacker, Samuel
Abstract: This essay lays out three kinds of corruption—personal, structural, and civic—stressing the differences among these phenomena. It then explores civic corruption via the work of the eighteenth-century Scottish thinker Adam Ferguson. Civic corruption occurs when the citizens of a republic lose interest in defending their shared institutions, and pursue their private wealth alone; avoiding it, according to Ferguson, requires placing limits on these private pursuits and getting citizens to participate in the public realm instead. By way of a comparison with Ferguson's contemporary and friend Adam Smith—who agreed with Ferguson on many issues, although not on what was corrupting about the acquisition of wealth—the essay argues that Ferguson, for all his emphasis on participatory government, was a liberal, not a collectivist. With that in mind, the essay endorses many of Ferguson's suggestions from a liberal perspective, and argues that, to preserve liberal republics, it is often necessary to expand what governments do, so as to maintain the commitment of citizens to their public institutions. This prescriptive implication brings out sharply how civic corruption differs from personal corruption, which may best be limited by shrinking the role of government, rather than expanding it.